Cloning and characterization of r3b; members of the r3 superfamily of late blight resistance genes show sequence and functional divergence - Li, Guangcun; Huang, Sanwen; Guo, Xiao; Li, Ying; Yang, Yu; Guo, Zhen; Kuang, Hanhui; Rietman, Hendrik; Bergervoet, Marjan; Vleeshouwers, Vivianne G G A; van der Vossen, Edwin A G; Qu, Dongyu; et al. (Molecular plant-microbe interactions, 2011)
Massive resistance (R) gene stacking is considered to be one of the most promising approaches to provide durable resistance to potato late blight for both conventional and genetically modified breeding strategies. The R3 complex locus on chromosome XI in potato is an example of natural R gene stacking, because it contains two closely linked R genes (R3a and R3b) with distinct resistance specificities to Phytophthora infestans. Here, we report about the positional cloning of R3b. Both transient and stable transformations of susceptible tobacco and potato plants showed that R3b conferred full resistance to incompatible P. infestans isolates. R3b encodes a coiled-coil nucleotide-binding site leucine-rich repeat protein and exhibits 82% nucleotide identity with R3a located in the same R3 cluster. The R3b gene specifically recognizes Avr3b, a newly identified avirulence factor from P. infestans. R3b does not recognize Avr3a, the corresponding avirulence gene for R3a, showing that, despite their high sequence similarity, R3b and R3a have clearly distinct recognition specificities. In addition to the Rpi-mcd1/Rpi-blb3 locus on chromosome IV, the R3 locus on chromosome XI is the second example of an R-gene cluster with multiple genes recognizing different races of P. infestans.